2003
DOI: 10.1172/jci200316233
|View full text |Cite
|
Sign up to set email alerts
|

Vpr R77Q is associated with long-term nonprogressive HIV infection and impaired induction of apoptosis

Abstract: The absence of immune defects that occurs in the syndrome of long-term nonprogressive (LTNP) HIV infection offers insights into the pathophysiology of HIV-induced immune disease. The (H[F/S]RIG)2 domain of viral protein R (Vpr) induces apoptosis and may contribute to HIV-induced T cell depletion. We demonstrate a higher frequency of R77Q Vpr mutations in patients with LTNP than in patients with progressive disease. In addition, T cell infections using vesicular stomatitis virus G (VSV-G) pseudotyped HIV-1 Vpr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
94
2

Year Published

2005
2005
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 26 publications
(10 reference statements)
7
94
2
Order By: Relevance
“…Thus, the apoptogenic effect of Vpr is only revealed when using pseudotyped viruses, that is genetically modified HIV-1 strains in which the endogenous Env gene has been replaced by nonapoptogenic Env proteins from other viruses. 8,11 This underscores the idea that Env is, at least in vitro, the principal apoptosis-inducing protein encoded by the HIV-1 genome. [12][13][14][15] The Env glycoprotein (gp) precursor protein (gp160) undergoes proteolytic maturation to generate gp41 (membrane inserted) and gp120 (membrane inserted or shed from the cell surface).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Thus, the apoptogenic effect of Vpr is only revealed when using pseudotyped viruses, that is genetically modified HIV-1 strains in which the endogenous Env gene has been replaced by nonapoptogenic Env proteins from other viruses. 8,11 This underscores the idea that Env is, at least in vitro, the principal apoptosis-inducing protein encoded by the HIV-1 genome. [12][13][14][15] The Env glycoprotein (gp) precursor protein (gp160) undergoes proteolytic maturation to generate gp41 (membrane inserted) and gp120 (membrane inserted or shed from the cell surface).…”
Section: Introductionmentioning
confidence: 91%
“…5,6 Clinical case reports 7 and epidemiological data 8 that await confirmation suggest that loss-of-function mutations affecting the apoptogenic action of Vpr 9,10 are more frequent in viral isolates from long-term nonprogressors (untreated patients with diagnosed HIV-1 infection for 410 years, with CD4 T cell count of 4500 Cells/ mm 3 ) than in patients developing AIDS. Conversely, mutations that truncate the putative glutathion peroxidase gene tend to be more frequent in AIDS patients than in long-term nonprogressors (Cohen et al, 2004), again underscoring the notion that a higher apoptogenic (or a lower antiapoptotic) potential of HIV-1 accelerates AIDS pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, mutations to key amino acids of Vpr have been associated with long-term nonprogressive HIV infections. 4 Second, patient-erived viral isolates with normal capability to replicate but without cytotoxicity have been described. These viruses contain Q3R mutations and premature stop codons in vpr.…”
Section: Introductionmentioning
confidence: 99%
“…Vpr was shown to locate predominantly in the nucleus or at the nuclear membrane [25,53,54], but not in the mitochondria. In addition, it has been reported that Vpr activates caspase-8 [55,56] which should not be activated in the intrinsic MOMP pathway.…”
Section: Viral Protein R (Vpr)mentioning
confidence: 99%